2021
DOI: 10.6007/ijarbss/v11-i4/9769
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in eHealth Literacy: Empirical Evidence from Turkey

Abstract: People in the world became more eager to use digital health services and search health information online more often with the effect of COVID-19. Even before the pandemic, Turkish people started to use the Internet as a source for getting health related information according to Turkish Statistical Institute data. There is always some difference between men and women in various attitudes, perceptions, or behaviors. It is believed that gender also matters while searching health related information. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The current study found that women were more likely to have higher eHealth literacy regarding COVID-19. This concurred with findings of previous studies 20,21 . Several studies found females were more willing and skilled to search health-related information online 27,28 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study found that women were more likely to have higher eHealth literacy regarding COVID-19. This concurred with findings of previous studies 20,21 . Several studies found females were more willing and skilled to search health-related information online 27,28 .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies, mainly in Western countries and primarily concerning chronic disease, have explored factors related to eHealth literacy in patients and health professionals, and they include sex, age, education, and social support 18–20 . In the context of COVID-19, an online survey in Turkey found that women had higher eHealth literacy than men, and women felt more confident and skilled for searching health-related information online 21 . A Web-based survey conducted in the United States showed the Black race and participants with lower education levels were associated with low coronavirus-related eHealth literacy 16 .…”
mentioning
confidence: 99%
“…Similarly, a study in Germany found that older female adults had lower levels of HL [38]. On the other hand, the study of Ozen [39] on gender diferences in eHealth literacy in Turkey reported higher levels of eHealth literacy in female participants. Unlike our fndings, a number of studies reported higher levels of SA in female participants [30,40].…”
Section: Discussionmentioning
confidence: 92%
“…Regarding gender, our findings are congruent with others which also explore the eHLQ among Nordic samples (Holt et al, 2019, 2020), suggesting weak relationships between gender and eHealth literacy. However, the literature is overall inconsistent in its reporting of gender and eHealth literacy (Huang et al, 2020; Ozen, 2021). Furthermore, our findings are in contrast with some (Paige et al, 2018), but consistent with others using the eHLQ among Nordic adults (Holt et al, 2019, 2020), in showing no strong relationship between age and eHealth literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender, our findings are congruent with others which also explore the eHLQ among Nordic samples (Holt et al, 2019(Holt et al, , 2020, suggesting weak relationships between gender and eHealth literacy. However, the literature is overall inconsistent in its reporting of gender and eHealth literacy (Huang et al, 2020;Ozen, 2021).…”
Section: Ta B L E 2 Descriptive Statistics On the Ehlq Domainsmentioning
confidence: 99%